If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3 + -5 + -4 Combine like terms: 3 + -5 = -2 y = -2 + -4 Combine like terms: -2 + -4 = -6 y = -6 Solving y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -6
| 13-5x=21-4x | | 0=5x+1 | | 10x-10=8x-5 | | -3x/4=5 | | 4x+14y=38 | | -10-6x=14-9x | | -x+9y=-10 | | (3+x)2=3x-1 | | 7(y)+4(4)=-28 | | 4x-11=3x-17 | | (5/3x)15/4 | | x+15x+50=180 | | 8x^2+4x=-15 | | X-7.5=9 | | 8x^3+20x^2-12x=0 | | 5/3x15/4 | | {3}{4}z={3}{4} | | 4-3=7 | | (e^3x+5)=12 | | 7(-7)+4x=-28 | | 38/1.62=x/1.00 | | e^3x+5=12 | | 3x+19=58 | | -7x-5=-5 | | 6c*2d= | | 2(2x-1)=x-7 | | 5a*4b= | | -85-10x=98-31x | | 40/1.62=x/1.00 | | 6x+3+6=x-4-2 | | -6.2x-(x-7)=34.6 | | 19x-15=-156 |